Welcome to the United States of anxiety : observations from a reforming neurotic - Lancaster, Jen, 1967- (New York : Little A, 2020)
Presents a witty assessment of today's high-anxiety world and offers advice on how to escape the impossible, judgmental standards of social media to unashamedly embrace the imperfectly human self.
Includes bibliographical references.
Keywords: Anxiety -- Popular works; Social media -- Psychological aspects